Technology of interview and ethical aspects of coverage of the theme of human trafficking in the printed media of Uzbekistan and Russia - Bozorova, Makhzuna Alijon qizi (Journal of the Belarusian State University. Journalism, 2019)
The world community has been confronted with the problem of human trafficking throughout history. In the twenty-first century human trafficking has become one of the most sophisticated forms of international crime. The victims of traffickers with «living» commodity become people of different nationalities, of any age, gender, different social and educational levels. There is a special responsibility on the media not only for the correct coverage of the given problem because of its public status and functional purpose, but also for effective interaction with sources of information, in particular, with the victims of human trafficking. The novelty of the research lies in the fact that the author for the first time conducts a comparative analysis of materials on this topic, published in the Uzbek and Russian press. Technology of interview as well as the ethical aspects of covering the topic of human trafficking are discussed. The main conclusions and recommendations on optimization of journalistic work in this area are given.